The Distribution of Surface Pollen in the Vertical Vegetation Zone of the Wuyi Mountains in Subtropical Southern China - Long Xiangyue; Huang Kangyou; Chen Cong; Xie Dehao; Shui Kunchun; Li Hongwei; Zheng Zhuo (Redai dili, 2023)
The Wuyi Mountains preserve the most complete central subtropical forest ecosystem in the subtropical zone, where the vegetation and soil have a distinct vertical distribution with elevation. To investigate the relationships between surface pollen assemblages and vegetation in this area, 76 samples of modern surface pollen with minimal human interference were collected from various elevations in the Wuyi Mountains. Based on the results of cluster analysis and redundancy analysis (RDA), this study indicates the connections between the distribution of pollen taxa at different elevations and under different climatic factors. The primary findings are outlined as follows: 1) Pinus, Castanopsis/Lithocarpus, Cyclobalanopsi, Quercus (evergreen), Taxodiaceae, Schima, Rutaceae, Ilex, Rosaceae, Poaceae, and Artemisia were the dominant pollen taxa, generally corresponding to the modern subtropical broadleaved evergreen forest. The pollen assemblages showed clear changes with variation in altitude; the relationships between pollen taxa and elevation were divided into three patterns: The low altitude areas (0-450 m) had a high percentage of Castanopsis/Lithocarpus, Quercus (evergreen), Theaceae, Schima, Ilex, Poaceae, and Dicranopranis. In the middle elevation area (450-1,850 m), Castanopsis/Lithocarpus, Pinus, Taxodiaceae, Tsuga, and Quercus (evergreen) were common. The higher altitude area, at approximately 1,850-2,200 m, was characterized by the dominance of Pinus, Poaceae, and Dicranopteris. 2) The results of RDA and cluster analysis divided surface pollen samples into different communities. RDA results also showed that the mean annual temperature, mean annual relative humidity, mean annual precipitation, mean precipitation of the coldest season, and mean precipitation of the warmest season were the main climatic factors that controlled the distribution of modern pollen. 3) The results of the representative analysis of pollen showed that Castanopsis/Lithocarpus, Pinus, Quercus (evergreen), and Artemisia were over-represented, and the genera Tsuga and Poaceae were represented less; 4) lower elevations had a significant presence of Poaceae, Artemisia, and Pinus. The pollen content of Quercus (evergreen) was low and the pollen type was relatively simple; it was related to the development of artificial pinewood in the foothills and the high spore content in the secondary forest, which indicated heavy human activity in the low altitude area. Therefore, these results revealed that the surface pollen assemblage varied significantly through the vertical vegetation zones in Wuyi Mountains of south subtropical China. The characteristics of surface pollen distribution were mainly affected by vegetation composition, habitat, and human activities, which is a crucial reference for reconstructing the paleovegetation and paleoenvironment in this region and similar areas.